ANALYSIS OF FACTORS AFFECTING THE STOCK SPLIT Case Study On Listed Companies In Indonesia Stock Exchange 2006-2010 - Praditya, Dimas; Affandy, Didied Poernawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research is to know about anything that affects the stock split on companies listed on the Stock Exchange. Each company was founded with the hope that the company can sustain its business, growing rapidly and can exist for long periods. Supporting operations require one financing for companies that have gone public by issuing shares to increase liquidity and trading perform stock splits, stock split is to break a piece of stock into n shares, price per new share after the stock split is 1 / n of the previous price. Basically there are two types of stock splits do, which is share split up (split up) and dropped the stock split (split down). Solving stock up or split up is the decline in the nominal value per share, which resulted in increasing the number of shares outstanding. Stock split or split down fall is the increase in the nominal value per share, and reduce the number of shares outstanding. There are several theories that explain the stock split and its relation to the stock price and liquidity. Among them there are two well-known theories as literature, the signaling theory and optimal trading range theory. Signaling theory or also known as information asymmetry states that a stock split provides an informative signal to investors about the prospects for improvement in the future returns which substantially while trading range theory states that the stock split will increase the liquidity of stock trading Keyword:Stock Split, Split Up, Split Down Singnaling Theory, Trading Range Theory